Design A CPW Fed Implantable Antenna at frequency 2.4 GHz for Wireless Implantable Body Area Network. Issue 1 (September 2020) - Ramli, N.H.; Othman, Hazila; Hamzah, Dayang Khadijah
Abstract: Designing implantable antenna is quite challenging due to the effect of lossy environment, necessity of small size and low power consumption and sequence of multipath losses. Thus, compact, small size and better performance are required for an antenna to operate in such systems. In this paper, the implantable antenna is designed by implemented coplanar waveguide (CPW) fed technique to enhances the antenna performances at frequency 2.4 GHz. The antenna performances are evaluated in term of return loss, gain, efficiency, radiation pattern. As the antenna is designed for wireless implantable body area network, hence, the antenna is tested in lossy environment. In this case, the antenna is submerged into a canola oil as it's dielectric properties represent a human breast fat. The propagation links between antenna inside human body phantom and antenna in free space environment are evaluated. The simulated and measurement results are in good condition. The results of the investigation can be a references in the future.